Strategic Research on Construction and Promotion of China's Intelligent Cities General Report - Pan, Yunhe (Strategic Research on Construction and Promotion of China's Intelligent Cities, 2018)
This book includes a general overview of the book series and summarizes the research results in its 13 subtopics. It systematically elaborates on how the construction and promotion of intelligent cities with Chinese characteristics could be implemented in the course of intelligent urbanization in China. Furthermore, it presents a variety of literature on urban management innovation and development, making it a valuable reference source on both the theoretic and empirical development of the new urbanization in China for intelligent-city decision-makers, c-level directors and officials in urban economy, social and environment departments and institutions all over the world.